The quality of image encryption techniques by reasoned logic - Marwah Kamil Hussein; Kareem Radhi Hassan; Haider M. Al-Mashhadi (Universitas Ahmad Dahlan, 2020)
One form of data is digital images, because of their widespread of frequent exchange over the internet it is necessary to preserve the security and privacy of the images transmitted.There are many image encryption techniques that have different security levels and there are many standards and protocols fortesting the quality of encryption security. The cipher images can be evaluated using various quality measuring criteria, these measures quantify certain features of the image. If there are many methods that can be applied to secure images; the question is what is the most powerful scheme that can be use damong these methods? This research try to answer this question by taking three different encryption methods (rivest cipher 5 (RC5), chaotic and permutation) and measure their quality using the peek signal to noise ratio (PSNR),correlation, entropy, number of pixels changes rate (NPCR) and unified average changing intensity (UACI), the results of these criteria were input to a fuzzy logic system that was used to find the best one among them.